Kualitas hidup remaja dan konsumsi alkohol di SMA Negeri 7 Manado pada masa COVID-19 - Ilham Maulana Zakaria; Gustaaf A. E Ratag; Dina V. Rombot (UNIVERSITAS SAM RATULANGI, 2022)
Background: Adolescance is a transitional period that creates significant change of physical, psychological, environment and social that can determine the quality of human life so that adolescents need a place to chanel theie mental turmoil due to these change. The role of school as a protection mechanism for adolescents during a pandemic has become less effective then can lead them to the various problems including alcohol consumption.Aim: This study aims to describe the quality of life and alcohol consumption of the student of SMA Negeri 7 Manado during the COVID-19 pandemic.Methods: This research is descriptive with a cross sectional design and has been conducted from September to December 2020. By using the stratified random sampling method, it has been found that 93 respondents met the inclusion and exclusion criteria.Results and Conclusion :The results showing that the quality of life of SMA 7 Manado adolescents, both girls and boys, is in the moderate category, this has been seen in the physical domain of men that is (66.71%), psychological (52%), social (58.26%), the environment (67.98%). Physical domain is in female students (67.5%), psychological (57.84%), social (60.85%), and environment (67.98%). Alcohol consumption of adolescents in SMA 7 Manado is still in the low category, that is (14%).Keywords: quality of life, adolescents, alcohol, COVID-19, pandemic